Sequential release kinetics of two (gentamicin and BMP-2) or three (gentamicin, IGF-I and BMP-2) substances from a one-component polymeric coating on implants - Strobel, Catrin; Bormann, Nicole; Kadow-Romacker, Anke; Schmidmaier, Gerhard; Wildemann, Britt (Journal of controlled release, 2011)
The local application of antibiotics in combination with timely controlled growth factor delivery might be beneficial for the prevention of infections and to stimulate bone healing. Therefore, in this study a variable sequential drug delivery system with three distinctly different release profiles was developed: i) a burst release of gentamicin, ii) a burst release of IGF-I followed by a sustained release, and iii) a slow sustained release of BMP-2 out of an implant coating. Only one polymer [poly(D,L-lactide)], incorporating gentamicin, IGF-I or BMP-2, was used for two- or three-layer coatings of K-wires. To control the release kinetics, the polymer concentrations in the solvent were varied. The activity of early released gentamicin from a two-layer coating was confirmed microbiologically and BMP-2 stimulated the metabolic activity and alkaline phosphatase activity of C2C12 cells after 2weeks. From the three-layer coated wires, IGF-I continuously stimulated the cell proliferation, whereas BMP-2 enhanced ALP between 1 and 3weeks. The sequential release of growth factors revealed an additive effect on the metabolic activity and ALP of primary osteoblast-like cells compared to the single coated controls. The controlled delivery of different factors from one implant might prevent infections and subsequently stimulate the different phases of bone healing.
Gesehen am 24.10.2022